Efficacy of neoadjuvant immunochemotherapy in locally advanced esophageal squamous cell carcinoma: a prospective cohort study with propensity-score matching - Zhang, Shifa; Hu, Anhao; Sun, Jiuhe; Wei, Yutao; Zhang, Jishan; Cai, Haibo; Wang, Gongchao (Frontiers in Immunology, 2026)
BackgroundThis study compared the efficacy of neoadjuvant immunochemotherapy (nICT) followed by surgery versus upfront surgery for locally advanced esophageal squamous cell carcinoma (ESCC).MethodsIn this prospective controlled trial (2020-2025), 623 stage II–IIIB ESCC patients were included; 192 received nICT (cisplatin, nab-paclitaxel, sintilimab) before surgery, and 431 underwent direct surgery. Propensity-score matching (PSM) and overlap weighting were used to adjust for baseline confounders.ResultsAfter PSM (144 pairs), the nICT group showed significantly improved progression-free survival (PFS; HR = 0.31, p<0.001) and overall survival (OS; HR = 0.42, p=0.002) compared to the upfront surgery group. The nICT group also had higher 1-/3-year PFS (88.8%/84.3% vs. 68.1%/52.8%) and OS rates (94.8%/84.7% vs. 89.6%/65.2%). Sensitivity analysis using overlap weighting confirmed these robust findings (PFS: HR = 0.37, p<0.001; OS: HR = 0.62, p=0.033).ConclusionsFor locally advanced ESCC, neoadjuvant immunochemotherapy significantly improves both PFS and OS compared to upfront surgery, establishing it as a highly effective treatment strategy.